DESIGN OF CO-WORKING SPACE & CAFE WITH THE APPLICATION OF TROPICAL ARCHITECTURE IN BINJAI CITY - Tok Tasya Stefhanie; Faurantia Forlana Sigit; Wahyu Hidayat (Bajang Institute, 2021)
The common activities of working and learning, usually carried out in office spaces and classrooms, sometimes create boredom for employees and students. To alleviate this monotony and pressure in work, co-working spaces & cafés are built with the aim of supporting work and learning activities in a flexible and dynamic environment. These spaces cater to various needs such as writing, teamwork, exchanging ideas, and interacting, providing a solution to both office and learning requirements. The design method applied involves a cyclical process that begins with the problem of how to utilize space to support work and learning activities in a more relaxed atmosphere. The proposed design concept for the co-working space & café is intended to address these initial challenges. The tropical architecture concept used in this design draws inspiration from the transformation of the Rumah Manka in two stages: the needs of working and learning activities, and the requirements for relaxation and commercial activities.